2022
DOI: 10.1002/bies.202200040
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm shifts in animal epigenetics: Research on non‐model species leads to new insights into dependencies, functions and inheritance of DNA methylation

Abstract: Recent investigations with non-model species and whole-genome approaches have challenged several paradigms in animal epigenetics. They revealed that epigenetic variation in populations is not the mere consequence of genetic variation, but is a semi-independent or independent source of phenotypic variation, depending on mode of reproduction. DNA methylation is not positively correlated with genome size and phylogenetic position as earlier believed, but has evolved differently between and within higher taxa. Epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 131 publications
0
3
0
Order By: Relevance
“…Clonally reproducing organisms, which lack meiosis, may exhibit less epigenetic reprogramming and thus more faithful transmission of DNA methylation across clonal generations compared to sexually reproducing species (Latzel et al., 2016 ; Latzel & Klimešová, 2010 ; Verhoeven & Preite, 2014 ). In both plants and animals, this extensive inheritance of DNA methylation could potentially account for the ecological success of clonal species, which often display broad natural distributions even in the absence of substantial genetic variation (Dodd & Douhovnikoff, 2016 ; Vogt, 2022 ). However, some epigenetic reprogramming associated with development is expected even across clonal generations, and definitive evidence for the higher stability of epigenetic modifications across clonal generations compared to sexual generations remains elusive.…”
Section: Composition Setting and Resetting Of The Epigenomementioning
confidence: 99%
“…Clonally reproducing organisms, which lack meiosis, may exhibit less epigenetic reprogramming and thus more faithful transmission of DNA methylation across clonal generations compared to sexually reproducing species (Latzel et al., 2016 ; Latzel & Klimešová, 2010 ; Verhoeven & Preite, 2014 ). In both plants and animals, this extensive inheritance of DNA methylation could potentially account for the ecological success of clonal species, which often display broad natural distributions even in the absence of substantial genetic variation (Dodd & Douhovnikoff, 2016 ; Vogt, 2022 ). However, some epigenetic reprogramming associated with development is expected even across clonal generations, and definitive evidence for the higher stability of epigenetic modifications across clonal generations compared to sexual generations remains elusive.…”
Section: Composition Setting and Resetting Of The Epigenomementioning
confidence: 99%
“…Recent cellular transcriptomic evidence reveals chromatin modifiers among the markers of animal stem cells on a broad evolutionary timescale, which suggests a pan‐metazoan epigenetic control of cell stemness (see above; Cazet et al, 2022; Sogabe et al, 2019; Tarashansky et al, 2021). It is becoming clear that epigenetic modifications are universally employed by most animals and beyond for executing deeply conserved regulatory functions, including expression control of evolutionarily old genes, as well as that these marks play vital evolutionary roles by establishing epigenetic memories inheritable across generations (Keller et al, 2016; Vogt, 2022; Zemach et al, 2010). In jawed vertebrates (at least osteognathostomes), parental epigenetic settings are reset in the starting embryo via global DNA rehypermethylation or active local methylation of enhancer regions, which leads to their ‘dememorization’ and prevents premature, ectopic (and fatal to the embryo) firing of adult, tissue‐specific enhancers and genes in early embryogenesis (X. Wu et al, 2021).…”
Section: An Evolutionary Concept Of Cell Typementioning
confidence: 99%
“…The critical role of terminal selectors in dictating cell identity has been extensively documented and experimentally verified in various biological settings, including the conversion of fibroblasts to striated muscle cells (Davis et al, 1987), neural and ectoderm specification (Deneris & Hobert, 2014;Dillon et al, 2022;Leon et al, 2022), as well as the prominent involvement of homeodomain TFs (e.g., HOX proteins) in a plethora of biological processes during embryo-and organogenesis, axial and tissue patterning, limb formation and so on (e.g., Bürglin & Affolter, 2016). Many TFs predate the Metazoa in evolutionary origin (e.g., Brunet & King, 2017, 2022de Mendoza & Sebé-Pedrós, 2019;Fairclough et al, 2013;Grau-Bové et al, 2017;López-Escardó et al, 2019;Sebé-Pedrós & de Mendoza, 2015;Sebé-Pedrós et al, 2016) and act deep within primal cell plasticity control mechanisms. It has been demonstrated that forced expression/ activation or repression/disturbance of (sometimes single) key TFs is sufficient to alter cell identity, change cell-fate decisions along the differentiation route or even return the cell to totipotency, a baseline, early blastomere-like state with unrestricted potential to reproduce all cell lineages and give rise to a clonal embryoid (e.g., Amadei et al, 2022;de Silva et al, 2022;DuBuc et al, 2020;Graf & Enver, 2009;Lau et al, 2022;Minnoye et al, 2020;E.…”
Section: Molecular Signatures Of Cell Identitymentioning
confidence: 99%
“…Both flexible and stable DNA methylation have phenotypic consequences. As the effects of DNA methylation on phenotypes have been reviewed and is not the focus on the current manuscript, the discussion below is not exhaustive [ 68 , 69 , 70 , 71 ].…”
Section: Implications Of Dna Methylation Within and Across Generationsmentioning
confidence: 99%